(untitled) (Eurasian Medical Research Periodical, 2022)
Long-lived multicellular parasites known as helminths cause their hosts’ immune systems to respond strongly and distinctly. The buildup of parasite loads over time, the infection’s chronicity recurrence, and the dominant function of immunity in pathogenesis are typical characteristics of helminth infections